POLYMORPHISM OF THREE LOCI INFLUENCE ON GROWTH TRAITS IN LOCAL QUAIL - KareemM. Hamad; Yousif M.S. AL-Barzinji (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The study aimed to find association between GH, IGF-I and PRL loci with body weight traits in local quail. Three hundred of three lines of local quail were used in the study. The molecular results showed polymorphism for all loci. The five, four and five alleles for GH, IGF-I and PRL locus, respectively were recorded. The allele D of GH, allele A of IGF-I and allele E of PRL locus have positive effect on growth and carcass traits in local quail lines. Based on the results, the CDCDCE genotype of all loci in desert quail significantly gives highest average daily gain (4.75g/ bird/day) and live body weight (208.18 g / bird /day) at marketing age. While the BDBCBE genotype in brown quail gives highest carcass weight (143.55g/bird) and dressing percentage (78.87%). These results show the possibility of rapid improvement and increase of local quail meat production through the selection of distinct alleles and genotypes that affect the growth and production of local quail meat